Improving Students’ Reading Comprehension of Recount Text Through Listen-Read-Discuss Strategy (LRD) : (A Classroom Action Research on the Eighth Grade Students of Junior High School 1 Anjungan in The Academic Year of 2022/2023) - Amaliya, Rizki Nova Mayori; Eusabinus Bunau; Ikhsanudin; Endang Susilawati; Dwi Riyanti (Kirana Publisher (KNPub), 2023)
The objective of this study was to improve student’s reading comprehension of recount texts through the use of the Listen-Read-Discuss strategy to address issues that were discovered in the classroom. The eighth-graders in this study were focused on, particularly those in class VIII E, which included 30 students. Action research in the classroom was used for this study. An observation checklist, field notes, and tests were the tools utilized in collecting the data. The researcher combined qualitative and quantitative data to analyze the data and examined the observation checklist with field notes for qualitative data. Moreover, the researcher examined the test that was determined by the mean score for each cycle in qualitative data. Based on qualitative data, this research concluded that students' reading behavior in the classroom improved through the Listen-Read-Discuss teaching and learning process. The student's performance increased from the first cycle to the second cycle, as evidenced by the observation checklist and field notes. Quantitative data results also revealed an improvement in the students' reading comprehension mean scores from the first to the second cycles. Based on the result, the researcher advises teachers to use strategies to teach reading comprehension based on the findings provided in this research report. It can help students who have trouble comprehending the text to understand better and increase their comprehension of the material taught.